Analisis Keadilan Sosial dalam Praktik Hukum Hak terhadap Manusia - Faturohman Faturohman; Charles Frisheldy Nainggolan; Rahmad Hidayat (Demokrasi: Jurnal Riset Ilmu Hukum, Sosial dan Politik, 2024)
Social justice is a very basic principle in the implementation of law regarding the rights possessed by every human being in Indonesia. These rights and social justice are related to each other, these rights aim to provide a very basic framework for the protection that every human being has against oppression and discrimination. The most important aspect of this right that every human being has is to a justice system that is carried out as fairly as possible. This social justice emphasizes the importance of ensuring that this access is not only formal, but can also be realized in practice in everyday life. These human rights function as a public policy that has the aim of achieving social justice.